An accurate analytical method for the determination of antimony in tea and tap water samples: photochemical vapor generation-atom trapping prior to FAAS measurement - Yazici, Elif; Buyukpinar, Cagdas; Bodur, Suleyman; San, Nevim; Komesli, Okan Tarik; Bakirdere, Sezgin (SPRINGER INT PUBL AG, 2021)
A sensitive and accurate sonication-assisted gas liquid separator-photochemical vapor generation-T-shaped slotted quartz tube with seven exit holes-atom trapping-flame atomic absorption spectrophotometry (SA-GLS-PVG-T-SQT-AT-FAAS) system was developed for the quantification of antimony at trace levels in daphne tea and tap water samples. A comprehensive univariate optimization was utilized to evaluate experimental conditions in terms of flame type, hydrogen gas flow rate, argon gas flow rate, trapping period, type of T-SQT and height of T-SQT. Under the conditions optimized, limit of detection (LOD) and limit of quantification values for the proposed method were figured out as 28.4 and 94.5 mu g/L, respectively. Increment in detection power was recorded as 96-folds when LOD values of the FAAS, and the SA-GLS-PVG-T-SQT-AT-FAAS systems were compared to each other. Spiking experiments were also carried out for the evaluation of the method's applicability and accuracy. Percent recovery results for both samples were found in the range of 90.2-108.0% using the SA-GLS-PVG-T-SQT-AT-FAAS system.
Keywords: T-shaped slotted quartz tube-atom trapping; Antimony; Flame atomic absorption spectrophotometry; Photochemical vapor generation; Chemistry